Manhood in crisis: powerlessness, homophobia and violence in Fight Club - Vafa, Amirhossein; Talif, Rosli (Universiti Putra Malaysia Press, 2011)
The following study will explicate how in Palahniuk's Fight Club, the narrator is in a certain crisis of manhood as a result of his contradictory experiences of power under the impositions of hegemonic masculinity, also aggravated due to a sense of disparity between his lived experiences and his inherited language of masculinity. As a response, the narrator sets out a nostalgic backlash to grapple with the outlets of the crisis-buried feelings, homophobia and aggression. While the backlashes materialize as transgressive assertions of manhood, the narrator becomes eventually disillusioned with his struggles and opts, instead, to come to terms with the crisis of manhood by forming an affectionate bond with Maria Singer, the only female character in the novel.